China and post-socialist development - Bolesta, Andrzej (Policy Press, 2015)
The re-emergence of China as an economic superpower during its systemic transition is an astonishing phenomenon. China and Post-Socialist Development is the first comprehensive attempt to frame China's advancements within the context of the East Asian developmental miracle, against the background of post-socialist transformation, asking how has it happened and where does China go from here? In this book the author argues that as China transits from central planning to market, it tries to imitate the institutions and policies of Japan and South Korea during their high growth periods of the second half of the twentieth century. China's approach - broadly in opposition to the neo-liberal doctrine - has brought impressive results, leading the author to make important predictions about the future. This book is for everybody who is interested in China, development and post-socialist transformation.